Expression, purification and characterization of three odorant binding proteins from the diamondback moth, Plutella xylostella. Issue 6 (19th August 2020) - Cai, L.; Cheng, X.; Qin, J.; Xu, W.; You, M.
Abstract: Odorant binding proteins (OBPs) are critical components in insect olfactory systems where they bind, solubilize and transport odorant molecules to receptors. Here, we cloned three OBPs (PxylGOBP1, PxylGOBP2 and PxylOBP24) from the diamondback moth, Plutella xylostella, one of the most destructive pests of cruciferous crops. These three OBPs were expressed in Escherichia coli as recombinant proteins, purified and characterized by fluorescence binding assays with 39 ligands including sex pheromone and plant‐derived chemical compounds. PxylGOBP1 and PxylGOBP2 showed significantly different binding affinities to theses ligands, suggesting distinct binding preferences of these two general odorant binding proteins. PxylOBP24 showed no or extremely low binding activities to selected ligands, suggesting it may be involved in non‐olfactory functions. Circular dichroism spectral results demonstrated that PxylGOBP1 and PxylGOBP2 shared similar secondary structures while PxylOBP24 was significantly different. This study improves our knowledge of insect OBPs, which will assist in a better understanding of insect olfactory system and developing more environmentally friendly pest control strategies for P. xylostella . Abstract : Three Plutella xylostella OBPs were cloned, expressed and purified. PxylGOBP1 and PxylGOBP2 showed significantly different binding affinities to sex pheromone components and plant‐derived compounds while PxylOBP24 did not show any binding activities to tested ligands. Circular dichroism spectral results showed that PxylGOBP1 and PxylGOBP2 shared similar structures while PxylOBP24 was significantly different.